Trocas turbulentas noturnas de CO2 entre a floresta de Uatumã, Amazonas, e a atmosfera - MAFRA, Ana Carolina Batista (Universidade Federal do Pará, 2018)
We study the nocturnal boundary layer - NBL above an area of primary tropical forest northeast of the state of Amazonas, the Sustainable Development Reserve of Uatumã, distant 15 km of the Uatumã River, located about 380 km northeast of the city of Manaus, Amazonas. It is intended to determine some of the characteristics of the NBL, particularly nocturnal turbulence regimes by identifying the differences related to vertical exchanges of CO2, according to the methodology proposed by Sun et al. (2012). Fast response data will be used for the atmospheric scalar and vector quantities, as CO2 concentration and wind speed, respectively. The methodology allows characterization of NBL in three regimes of dynamic stability: 1) weak turbulence, mean low wind speed; 2) strong turbulence, with high wind speed, and 3) intermittent turbulence events with "top -down ". From this characterization, we have investigated some of the main statistical characteristics of each turbulent regime. As would be expected, the turbulent fluxes of CO2 increases with the characteristic scale of turbulent velocity, VTKE, associated with turbulent kinetic energy measured above the forest canopy. The CO2 exchange increases considerably with the regime 2,with higher values of the mean wind speed, | V |, and with the occurrence of strong mixing in the atmospheric boundary layer, ABL, not predominantly generated by surface forcings .